In-situ (Ti, Nb)C reinforced Ni-based coatings: New insights into microstructure evolution, enhanced phase configuration behavior and tribological properties. Issue 9 (15th June 2020) - Zhang, Mingyang; Li, Min; Chi, Jing; Wang, Shufeng; Fang, Min; Zhou, Chao; Liang, Bin; Xue, Junxian
Abstract: Multiple carbide reinforced metal matrix composite coating has been a promising material with superior abrasion resistance properties. Currently the improvement of the wear resistance of metal matrix composite coating mainly depends on the introduction of reinforcing phase at the expense of the inherent excellent ductility of metal matrix. Here, a new window to enhancing the wear resistance by adjusting the configuration of reinforcing phase space without sacrificing the inherent toughness of the matrix is introduced. Multiple (Ti, Nb)C/Ni-based hardfacing alloy coating prepared by plasma transferred arc technology has been investigated in this paper. Results showed that with the change of Ti/Nb atoms ratio, Cr-rich carbide has an obvious refinement behavior, which changes from a thick slat shape to a short bar with a smaller length-diameter ratio. It is observed that the microcracks are generated from coarse Cr-rich carbide under the action of applied stress and expand rapidly. Nevertheless, with the refinement evolution of Cr-rich carbide shape, only tiny micro-cracks exist in Cr-rich carbide. When Ti:Nb = 7:3, the improvement of wear resistance of the coating was mainly attributed to the reasonable spatial configuration distribution of the enhanced phase. When Ti:Nb = 3:7 and 0:10, the improvement of wear resistance of coating was mainly attributed to the improvement of microhardness brought by the increase of carbide precipitation content. By designing the internal correlation between the spatial configuration behavior of reinforcing phase and dry sliding wear test, the positive correlation between wear resistance and microhardness of materials was broken, which may provide a design window for improving wear resistance while maintaining good toughness of matrix.